2011
DOI: 10.1074/jbc.m110.181206
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides Increase Tolerance to Oxidant Stress in Drosophila melanogaster

Abstract: It is well appreciated that reactive oxygen species (ROS) are deleterious to mammals, including humans, especially when generated in abnormally large quantities from cellular metabolism. Whereas the mechanisms leading to the production of ROS are rather well delineated, the mechanisms underlying tissue susceptibility or tolerance to oxidant stress remain elusive. Through an experimental selection over many generations, we have previously generated Drosophila melanogaster flies that tolerate tremendous oxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 67 publications
2
44
0
Order By: Relevance
“…One example could be antioxidants, the expression of which was previously shown to be induced or suppressed by activation or silencing, respectively, of the Toll pathway in A. aegypti . In Drosophila, overexpression of antimicrobial peptides increases antioxidant enzyme activities and changes the cellular redox balance, facilitating fly survival in hyperoxia (Zhao et al, 2011). Consistent with our observation in both WB1 and MGYP2 mosquitoes, previous studies also showed that antioxidant treatment resulted in increased Wolbachia density in Drosophila (Brennan et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…One example could be antioxidants, the expression of which was previously shown to be induced or suppressed by activation or silencing, respectively, of the Toll pathway in A. aegypti . In Drosophila, overexpression of antimicrobial peptides increases antioxidant enzyme activities and changes the cellular redox balance, facilitating fly survival in hyperoxia (Zhao et al, 2011). Consistent with our observation in both WB1 and MGYP2 mosquitoes, previous studies also showed that antioxidant treatment resulted in increased Wolbachia density in Drosophila (Brennan et al, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…Antioxidants, as potential effector molecules of boosted immunity, enhance Wolbachia infection in A. aegypti Overexpression of antimicrobial peptides was reported to increase tolerance to oxidant stress in Drosophila melanogaster (Zhao et al, 2011), and both wAlbB and boosting mosquito immunity were observed to induce the expression of antioxidants and antimicrobial peptides in A. aegypti . We speculated that boosting immunity enhances Wolbachia infection through alterations Figure 3 Boosted basal immunity promotes the growth of wAlbB in A. aegypti.…”
Section: Resultsmentioning
confidence: 99%
“…Assay was performed as described by Zhao et al (2010). In brief, 100 μl of fly homogenate was incubated with 10 μM DCFH-DA (in dimethyl sulfoxide) and fluorescence was measured using a microplate reader at an excitation and emission wavelength of 485 and 535 nm, respectively.…”
Section: Measurement Of Ros Generationmentioning
confidence: 99%
“…Oxidation of DCFH-DA (in terms of DCF fluorescence) was assayed as a measure of the general index of oxidative stress as described previously by Zhao et al [31]. In brief, 100 ml of fly homogenate (homogenization was performed for 30 s) was incubated with 10 μM dye (in dimethyl sulfoxide) for 30 min in the dark at 2471 1C and fluorescence was measured (60 s intervals) using a Varioskan Flash spectrofluorometer (Thermo Fisher Scientific, Waltham, MA, USA) at excitation/emission wavelengths of 485/535 nm.…”
Section: Assay For Oxidative Stressmentioning
confidence: 99%